Mitochondrial DNA indicate paraphyletic relationships and resolve disjunct distributions in the Neotoma mexicana species group - Hernández-Canchola, Giovani; León-Paniagua, Livia; Esselstyn, Jacob A. (THERYA, 2021)
Woodrats (genus Neotoma) comprise 24 species found primarily in the United States and México. The Neotoma mexicana species group reaches its southernmost distribution in the highlands of southern México and Central America. Previous research suggested that N. mexicana has a discontinuous distribution, whereas N. ferruginea and N. picta have allopatric distributions around the lowlands of the Isthmus of Tehuantepec. However, these hypotheses were suggested with incomplete subspecific sampling near the isthmus. We used samples of N. m. parvidens from the Sierra Sur de Oaxaca and N. m. tropicalis from the Sierra Norte de Oaxaca to assess their taxonomic affinity. Our phylogenetic analyses of the mitochondrial cytochrome-b gene place both subspecies in N. ferruginea. Therefore, we suggest that N. mexicana is continuously distributed from the United States to the Transmexican Volcanic Belt, N. picta inhabits the Guerreran Sierra Madre del Sur, and N. ferruginea ranges from the Oaxacan Sierra Madre del Sur to Central America. Our findings also indicate that the Isthmus of Tehuantepec did not promote speciation in these woodrats.